Three new ameirid harpacticoids from Korea and first record of Proameira simplex (Crustacea: Copepoda: Ameiridae) - Karanovic, Tomislav; Cho, Joo-Lae (Zootaxa, 2012)
Ameiridae Monard, 1927 was previously known from Korea only after one endemic and four cosmopolitan species of the genus Nitokra Boeck, 1865, and a single widely distributed species of the genus Ameira Boeck, 1865, all from brackish enviroments. After a survey of 22 sampling sites and close to 3,500 harpacticoid specimens from various marine enviroments, we report on two new endemic species of Ameira, A. zahaae sp. nov. and A. kimchi sp. nov., from the West Sea and the South Sea respectively. They are both relatively closely related to the previously recorded cosmopolitan A. parvula (Claus, 1866), but show many novel morphological structures in the caudal rami shape and ornamentation. The identity of the cosmopolitan A. parvula in Korea is questioned, and an alternative hypothesis of a species-complex proposed. The fine ornamentation of body somites (especially the pores/sensilla pattern) is studied in detail, and proves to be a very useful new morphological tool in distinguishing closely related spacies in this genus. The genus Pseudameira Sars, 1911 is reported for the first time in Korea, after four females of P. mago sp. nov. from the South Sea. A single damaged female of Proameira cf. simplex (Norman & Scott, 1905) represents the first record of the genus Proameira Lang, 1944 in Korea, Asia, and anywhere in the Pacific. A key to Korean ameirids is also provided, and their apparent rarity in this part of the world noticed.